2016
DOI: 10.15171/jrip.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Contrast induced nephropathy among patients with normal renal function undergoing coronary angiography

Abstract: Introduction: Although contrast induced nephropathy (CIN) is a well-known complication of radiocontrast media administration among patients with underlying renal insufficiency, however the data about CIN among patients with normal renal function are few and it seems that CIN often remained under-diagnosed among these patients. Objectives: The aim of present study was evaluation of CIN in diabetic and nondiabetic patients with normal renal function undergoing coronary angiography. Patients and Methods: This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…In the present study, the incidence of CIN occurred in 19 ( results in the present study showed even patients with normal kidney function have the development of CI-AKI after exposure to contrast media; this finding is agreed with Assareh et al 13 Recent study carried by Sato et al, showed that CIN was an independent predictor of subsequent renal events in the patients who underwent cardiac catheterization. 14 The risk of CI-AKI due to coronary angiography increases dramatically with low kidney function.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the incidence of CIN occurred in 19 ( results in the present study showed even patients with normal kidney function have the development of CI-AKI after exposure to contrast media; this finding is agreed with Assareh et al 13 Recent study carried by Sato et al, showed that CIN was an independent predictor of subsequent renal events in the patients who underwent cardiac catheterization. 14 The risk of CI-AKI due to coronary angiography increases dramatically with low kidney function.…”
Section: Discussionsupporting
confidence: 92%
“…This can be attributed to the volume of contrast agent in these procedures, as therapeutic intervention take longer duration that needs larger volume of contrast agent; this is supported by a study of Kane et al [10]. Similarly, in a retrospective study of nearly 104 patients who underwent diagnostic or therapeutic PCI, those with duration of procedure more than 90 minutes shown a higher risk of CIN development, also shown that use of more than 200 ml of contrast media was associated with further risk for development of CIN [10], and other studies correspond to these findings [30,33,39].…”
Section: Discussionmentioning
confidence: 61%
“…At present, hydration therapy is generally recognized as the routine measure to prevent CIN. Although adequate hydration therapy reduces the concentration and hyperosmotic state of the contrast media [29], the incidence of CIN after PCI is still high [30] and hydration therapy cannot decrease the production of oxygen-free radicals. As the contrast media can cause a series of oxidative stress reaction, several compounds with properties of antioxidant stress such as sodium bicarbonate, N-acetylcysteine, ascorbic acid, and statins have been investigated [31].…”
Section: Discussionmentioning
confidence: 99%